If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c = 4x + 5 Reorder the terms: c = 5 + 4x Solving c = 5 + 4x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Simplifying c = 5 + 4x
| X^4+10X^2+18=0 | | 3x-18=6x+21 | | 58.5=35x-6 | | a(12-n)= | | 9z+4-7z=49-7z | | 2(-3p-6)=3[-4p-3(p+2)] | | 28+36+6(-7x+x)=2(5x-6) | | -4p-5=15 | | -16tx^2+21x-6=0 | | 6(a-8)+16=4(a-7) | | 6x-4(6-x)=2 | | Cot3x/5=-1 | | 28+36+6(-7x+c)=2(5x-6) | | 32+2x=12-7x | | 5(4x-2)+6=-3 | | 3(c-1)+4=17-(c-4) | | -8-5y-5=11-9y-16 | | -1=6-2(3y+2) | | 4x-50=4-5x | | A=x+3+z | | 4.5z=4.5z-6.25+6 | | 5x+19=x+21 | | 15-5x=-7x+15 | | 4x+16-6=22+6 | | 2y^2=13y | | 11=7+2(3z+2) | | -5x=-7+2x | | 7x+52=9x+24 | | 4m-33=11 | | 4cos^2(2t)-4sin^2(2t)=4 | | 4x-19=1x-30 | | 8z-3=-59 |